Cost of Hematopoietic Stem Cell Transplant and Cytomegalovirus-related Complications in a Large Inpatient Claims Database. (4th October 2017) - Schelfhout, Jonathan; Brown, Harold; House, John
Abstract: Background: Cytomegalovirus is a major contributor to morbidity and cost following allogeneic hematopoietic stem cell transplantation (HSCT), yet scant data exists on the cost of HSCT and complications to the inpatient setting. The objective of this analysis is to explore rates of rehospitalization and inpatient cost associated with CMV during the first year following allogenic HSCT. Methods: Participants were identified from the Premier Healthcare Database who had an inpatient admission with an ICD-9 diagnosis code for allo-HSCT between 2006 and 2015. Total cost was calculated for the index hospitalization and first 100 days post discharge for participants with and without an ICD-9 code for CMV infection or disease. Results: There were 1731 participants included in the cohort, 161 (9.3%) of whom had at least one readmission during follow-up admission with a CMV ICD-9 code. Participants with CMV readmission during the first 100 days post-transplant had a greater total LOS following discharge (31.9 vs. 13.0 days; P < 0.001) and increased mortality rate (31.1% vs. 14.1%; P < 0.001) when compared with those without CMV infections. The average length of a CMV re-hospitalization was 31 days and the majority of patients were treated with ganciclovir (62.7%) followed by foscarnet (39.1%). The total cost of the first 100 days post-discharge was significantly greater in participants who had a CMV readmission compared with those without ($111, 729 vs. $46, 063). Conclusion: CMV represents a substantial economic burden to hospitals during the first 100 days following an HSCT procedure. Future strategies that minimize the risk of CMV infection and/or disease may result in significant economic benefit. Disclosures: J. Schelfhout, Merck: Employee, Salary. H. Brown, Merck: Research Contractor, Research support. J. House, Merck: Research Contractor, Research support